1988
DOI: 10.1111/aogs.1988.67.s145.9
|View full text |Cite
|
Sign up to set email alerts
|

PROPHYLACTIC USE OF 15(S)15 METHYL PGF2α, BY INTRAMUSCULAR ROUTE — A CONTROLLED CLINICAL TRIAL

Abstract: In a multicentre study the safety and efficacy of 125 µg intramuscular injection of 15(S)15 methyl PGF , (Prostin 15M, Upjohn) was compared with ergometrine and controls who did not receive any oxytocic for prophylactic control of postpartum bleeding. The study included 441 patients. The duration of third stage was shortened to 6.1 minutes following ergometrine and to 3.5 minutes following Prostin 15M compared to 7.6 minutes in the control subjects. Similarly the blood loss during third stage was less (95.2 ml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 5 publications
2
10
0
Order By: Relevance
“…The discovery of prostaglandins and their analogues as uterotonics has improved the management of PPH due to their significant influence on uterine tone, which results in minimizing the blood loss; this outweighs its cost. The side effects are also subtle [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of prostaglandins and their analogues as uterotonics has improved the management of PPH due to their significant influence on uterine tone, which results in minimizing the blood loss; this outweighs its cost. The side effects are also subtle [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that when prophylactic prostaglandin F2 alpha was given intramyometrially the blood loss and the length of the third stage was reduced compared with the prophylactic use of intravenous ergometrine (12). More recently, 2 trials have shown that blood loss in the third stage and its duration were significantly reduced when intramuscular prostaglandin 1 5-methyl F2 alpha was given prophylactically to a group of women who delivered vaginally compared with 2 groups of women who had prophylactic intravenous methyl ergometrine 200-400 ug, or no prophylactic oxytocics (13,14). No significant cardiovascular or gastrointestinal sideeffects were observed in the 2 trials.…”
Section: Discussionmentioning
confidence: 99%
“…10 In a study by Anjaneyulu et al the mean duration of third stage of labour in methyl ergometrine group was 6.1 minutes and in carboprost group was 3.5 minutes. 11 In another study by Purushotham BJ et al it was 3.6 minutes and 2.63 minutes for methyl ergometrine and carboprost tromethamine groups respectively. 12 In the present study mean blood loss in the third stage was 127.6±54.14.…”
Section: Discussionmentioning
confidence: 92%